Analysing FP7 from a systemic perspective: What role for the delineation and the set up of the sub-programmes? - Henning Kroll; Niclas Meyer (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2016)
[Introduction] The Seventh EU Framework Programme for Research and Technological Development (FP7) was one of the world's largest support programmes for research and development even though the sum of national research budgets in the EU is still higher. More than exteuro 55bn, the third largest section of the European budget, have been invested in knowledge, innovation and human capital with the declared objective to increase the potential for economic growth and to improve European competitiveness. In this effort, FP7 covered not only different themes and disciplines but addressed different stages of the innovation process and multiple, heterogeneous stakeholders. In the most general terms, the 7th Framework Programme, as its predecessor, was adopted as an instrument to support the integration of a "European Research Area" (ERA) (Chou, 2012), a "system of research programmes integrating the scientific resources of the European Union", one "in which researchers, scientific knowledge and technology circulate freely" and suitable to "strengthening [the Union's] scientific and technological bases" (European Commission, 2000). It is defined as a clear complement to national research policy while at the same time addressing the same resources and people - to build a robust, overarching innovation system of strong players with complementary capacities, well networked across national borders. In recent years, following FP7's formal conclusion, various evaluation studies have been published, which come to an overall favourable assessment of the programme's achievements. Without doubt, these are relevant, valid and this very paper builds substantially on the many findings that they have established. Until now, however, the internal structure of what we refer to as "the Seventh Framework Programme" remains underexplored. Despite the fact that it has now already been notably adapted for Horizon 2020, little empirical evidence is available on the extent to which its different lines sub-programmes complemented each other, resonated with national efforts and, in so doing, led to satisfaction or frustration among their consortiums of beneficiaries. [...]
urn:nbn:de:0011-n-3893284
Keywords: 330